Agricultural Show Awards: A Brief Exploration of Their Role Marketing Food Products. Issue 4 (1st October 2016) - Henryks, Joanna; Ecker, Saan; Turner, Bethaney; Denness, Bonnie; Zobel-Zubrzycka, Halina
ABSTRACT: Drawing on interviews with 12 agriculture show winners across a range of different food industries, this report provides a preliminary analysis of the role that agricultural show awards play in branding and marketing food products for commercial sale. In keeping with findings from previous studies, show awards were found to be regarded by producers as prestigious, signifying product excellence. Further, the assessment of the quality of products, the opportunity to receive expert feedback on new products, and a comparative, competitive effect of the show system was found to provide a mechanism to improve quality, helping to support industry standards and foster a culture of innovation. Show awards were identified as especially important in supporting small-scale entrepreneurial endeavors that depend on niche marketing strategies. However, winning awards was shown to contribute more to perceived brand equity of products rather than actual economic gain. To strengthen the impact of show success, participants indicated the need for increased consumer awareness of the meaning of the awards. The authors identify key future directions research could take to maximize the impact of agricultural award systems on the businesses of competitors.